THE RESULTS OF EXPERIMENTAL STUDIES OF CONCRETE STRUCTURES OF HYDRAULIC ERECTIONS REINFORCED WITH CARBON TAPE UNDER THE ACTION OF BENDING MOMENTS - O D Rubin; S E Lisichkin; K E Frolov (Structural Mechanics of Engineering Constructions and Buildings, 2016)
The reinforcement of concrete structures of hydraulic erections with carbon ribbons as external reinforcement system is proposed to carry out. The results of experimental studies of the strength of concrete structures of hydraulic erections without reinforcement and reinforced with carbon ribbons with bending moment are presented. The strength improvement by increasing with carbon ribbons is defined